Southern high-latitude vegetation and climate change across the Eocene and Oligocene and the role of the widening Tasmanian Gateway - Amoo, Michael (2022)
The shift from a greenhouse to an icehouse climate from the Eocene to the Oligocene is extensively documented by sea surface temperature records from the southwest Pacific and the Antarctic margin, which reveal evidence of significant long-term cooling. However, the identification of a driving mechanism (tectonic deepening of Southern Ocean gateways and/or declining pCO2 concentration) is contingent upon a greater comprehension of whether this cooling was also present in terrestrial environments. This study provides new records of Eocene to Oligocene vegetation and climate dynamics in the wider Australo-Antarctic region (southeastern Australia/Tasmania and New Zealand) in the context of the widening Tasmanian Gateway based on analyses of sporomorphs from ODP Site 1172, Site 1168, and TNW-1. Results from Tasmania showed a temperate Nothofagus-dominated rainforest with secondary Podocarpaceae (eastern Tasmania; ET) or Gymnostoma (western Tasmania; WT) during the late Eocene to Oligocene. Sporomorph-based climate estimates also showed a 2-3 °C terrestrial cooling (in ET) ~3 Myr prior to the EOT, coinciding with the regional Southern Ocean cooling known as the Priabonian Oxygen Maximum (PrOM); fluctuation between cool-and warm-temperate climate phases (ET & WT) coinciding with the initial deepening of the Tasmanian Gateway at ~35.5 Ma; ~2 °C cooling across the EOT, and a remarkable climate rebound in the early Oligocene coinciding with the global decline in pCO2 in the late Eocene and its recovery in the earliest Oligocene (ET and WT). However, the extended early Oligocene climate recovery seem to have resulted in a mismatch between pCO2 and sporomorph-based MATs in western Tasmania. Palynomorph-based biostratigraphic analyses of the TNW-1 drillcore in the Canterbury Basin, Southland, New Zealand, report a Porangan (middle Eocene) to Whaingaroan (late Oligocene) age, and assign a Whaingaroan age (early Oligocene) to the Marshall Paraconformity. The warm-temperate Casuarinaceae-dominated vegetation association of ...